Confronting inequality beyond sustainable development: The case for eco‐human rights and differentiation. Issue 1 (3rd April 2022) - Cullet, Philippe
Abstract: The development model emphasizing economic growth has been at the root of today's environmental crises. Its reshaping as 'sustainable' development was supposed to address its shortcomings while giving particular attention to the needs of the poor. This has largely failed and in the process inequalities have increased significantly. Inequalities between people need to be addressed through eco‐human rights that are collective and multi‐level to better reflect today's environmental challenges. These rights build on the idea of solidarity rights, are framed around the principle of subsidiarity and the need for accountability beyond a single State. Inter‐State inequality has been addressed in part through differential treatment in environmental law. It needs to be reconfirmed to address ongoing inequalities and increased resistance to such measures; needs to be more flexible to reflect the specific situation of smaller groups of countries; and needs to integrate elements of intra‐State inequality.